Customer Loyalty Research : The Cases of Existing E-Commerce Platforms - Dea Cyntika Usmed; Syafrizal; Alfitman; Fera Yuliani; Tedi Hidayat (Institute of Computer Science (IOCS), 2021)
Customer loyalty has become primary challenge to the existing e-commerce platforms in the competitive business environment. This research aims to determine the effects of several variables related elements to increasing customer loyalty in the digitalization, such as social media marketing, online customer experience, satisfaction, and positive word of mouth. We received 252 feedbacks, then the data were analyzed by assisting PLS 3.3 Software through the technique of SEM. We found there are fifth hypothesis in line with expectation, and two of them are rejected.